CHROMATIC COLORS IN GERMAN AND ENGLISH INTERIOR ADVERTISING - Совєтна, Альона; Совєтний, Едуард (Modern engineering and innovative technologies, 2022)
Advertising texts in German and English languages were analyzed, in particular red and yellow colors in interior advertisements. Red lexemes in the German language are not inferior to red in the Ukrainian language. Elements of national and cultural brandi